Analisis Studi Kelayakan Bisnis Usaha Fotocopy X Favourite Photo - Dini Vientiany; Deva Fitri Zuya; Mareta Rindiani; Sri Rapida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study evaluates the business feasibility of the printing and photocopy service enterprise “Fotocopy X Favourite Photo,” which is strategically located near a university and office area. The main issue addressed is the extent to which this business demonstrates sustainability potential in terms of market, financial, operational, and legal aspects amid intense competition. The objective of this study is to analyze the business feasibility based on these factors. This research employs a qualitative approach with a descriptive method, utilizing semi-structured interviews, a mini survey involving 50 customers, and direct observation, complemented by descriptive data analysis and source triangulation. The findings indicate that the business has significant growth potential, supported by high customer satisfaction, profitable financial performance, and adequate legal compliance. The main challenges identified include dependence on electricity and manual financial record-keeping. Future research is recommended to focus on developing digital marketing strategies and implementing innovative, system-based financial management to enhance competitiveness and long-term business sustainability.